An integrated conceptual model for predicting behavioral learning triggered by video-game engagement: A mediating role of observational learning - Abbasi, A.Z. (Institute of Electrical and Electronics Engineers Inc., 2015)
This study proposes a conceptual model that could predict how customers' engagement in video games influences them to learn through observing the models shown in the video games, which further impacts behavioral learning. This study reviews the stimulus response theory and observational learning theory, and draws an integrated conceptual model. This model theorizes that customers learn from observation of models portrayed in the video games triggered by their engagement in video games, which influences customers' behavioral learning. Propositions were also drawn on the basis of proposed model. This study is conceptual in nature and another subsequent study is required to validate the study propositions. This study contributes in the following domains; (a) stimulus response theory, especially in S-O-R paradigm by introducing factors affecting organism (O) in video game studies, (b) observational learning processes are integrated in S-O-R model as organism (O) that mediates the relationship between video-game engagement and behavioral learning, (c) customer engagement definition is being adopted in video game studies to theorize how customers' engagement in video games influences the observer to learn the behavior. This conceptual model will be very helpful in predicting various forms of learning through observation of the models, including a new pattern of behavior, judgmental-standards, cognitive-competencies, strengthen or weaken the existing behavior and generative guidelines for producing a new form of behavior. Â© 2015 IEEE.